Quality of Work Life on Performance Management - Oyomo, Angeline Atieno (Advances in Social Sciences Research Journal, 2017)
Worldwide, Quality of work life (QWL) has been viewed to include some objective and subjective factors which may condition operations and other inner aspects concerning the quality of relationships and methods of management. The study analyzes the quality of work life indicators in a cohort of department of health workers. Semi-structured interviews were conducted, to assess the quality of work life through the identification of the most important indicators and to evaluate the degree of Career Care Programs and the importance of each indicator. Target population was 300 employees with sample size of 180. The study pointed out some macro areas which are relevant to define work life quality of the analysed sample: relationships with colleagues, work organization, taking care of clients, professional ability and professional growth. The agile work environment, performance management, Social Service Care and the management styles seem to be important to determine the differences among the workers in the quality perceived in their work life. However, the study found out that there is low esteem among employees owing to the poor social service care, biased performance management and non-motivating reward systems. This could explain why employees come to work late and leave early yet at some point they are not in the office doing their personal activities during work time.